Oil Charging Power Simulation and Tight Oil Formation of Fuyu Oil Layer in Sanzhao Area, Songliao Basin - Si, Shanghua; He, Junhao; Liu, Ping; Liu, Jiexin; Yan, Gongjie; Yao, Qingtong; Yang, Yong; Chen, Xu; Liu, Chao (Frontiers in Earth Science, 2022)
A thermodynamic and hydrocarbon composition model based on VTFlinc software was conducted based on the homogenization temperature of fluid inclusions and gas-to-liquid ratio, and the fluid inclusions’ trapped pressure was calculated. This software does not require the determination of individual inclusions, the composition of the simulation procedure is simple, and the simulation result has certain reliability. The VTFlinc software was used to calculate the trapped pressure of oil inclusions in the Fuyu tight reservoir of the Sanzhao area in the Songliao Basin. The results show the existence of two phases of oil charge. The first phase occurred at the end of the Nenjiang Formation at 79–74 Ma with an oil entrapped pressure of 16.922–19.068 MPa, and pressure coefficient of 1.18–1.26. During the second period in the Sifangtai Mingshui group at 69–64 Ma, the oil entrapped pressure was 20.216–28.830 MPa, and the pressure coefficient was 1.21–1.33. During the two periods, the pressure of the trapped oil inclusions is abnormal, and the pressure coefficient is above 1.2. Abnormal high pressure is the main driving force of hydrocarbon source rock and oil in the Fuyu Formation, as well as an important driving force for the lateral migration of oil in the tight reservoir. The reservoir formation model of the Fuyu tight oil reservoir in the Sanzhao area is a direct high-pressure charging and multi-channel migration accumulation model. The Q-1 source rock and Fuyu oil layer has a direct contact relationship between the source rock and the reservoir.